Women Participation And Decentralised Politics - Dr. M. Yariswamy (Jai Maa Saraswati Gyandayini An International Multidisciplinary e-Journal, 2017)
The position of women in politics was analyzed a number of years ago in the well-known United Nations study edited by Maurice Duverger. Men continued to believe that political activity was a masculine Prerogative. The old theory of female incapacity had been replaced by a „functional‟ theory about the division of aptitudes, which is necessarily reflected in the division of labour. In its modernized form, this kind of functional theory recognizes the right of women to work outside the home and to participate in civic and political affairs, yet emphases their special concern with „home policy‟ matters, i.e., motherhood and its problems, education and the family. Women‟s political activity becomes channeled into these areas rather than into political parties, trade unions and the life. The best way to judge the position of a nation is to find out the status of women. In reality the status of women is the measuring rod for assessing the standard of culture of any age. The social status of women is a country- represents the social spirit of the age.